Objective measurement of Spanish emotion vocabulary - Delgado, Ana R. (2023)
Current research on emotion knowledge and competence emphasises the role of language. Emotion vocabulary is one of the indicators of emotion knowledge that can be objectively measured; however, the metric properties of the scores obtained in tests and tasks to measure it have seldom been adequate. In this study we designed and validated a Spanish emotion vocabulary test (MOVE) employing a corpus approach to construct cloze multiple-choice items, administered the test to a Spanish-speaking sample from two countries, Spain and Argentina, and analysed structural validity of the test items with the Rasch model measurement approach. Eighty-eight items showed adequate fit. Overall, a substantial percentage of variance was explained by a latent variable. Reliability indexes at the test, item, and person level were also adequate. As a vocabulary test, the MOVE can be used in psychological and neurological investigation, as well as in language learning research.